PENGARUH STRATEGI PEMASARAN DALAM MENINGKATKAN VOLUME PENJUALAN PADA TOKO ALVIAN RESA PRIANTO DESA AMBAIPUA KECAMATAN RANOMEETO KABUPATEN KONAWE SELATAN - Rendelangi, Aikal Bisma; Sahyunu, Sahyunu; Manan, Laode Abdul (Sultra Journal of Economic and Business, 2023)
The purpose of this study is "to determine the influence of marketing strategies in increasing sales volume at the Alvian Resa Prianto Store, Ambaipua Village, Ranomeeto District, South Konawe Regency. To test the proposed hypothesis, a partial t-test is used and to find out the form of influence of the free variable on the bound variable is used an analysis of the coefficient of determination. The population of this study is all consumers who shop at alvian Resa Prianto Store, South Konawe Regency. The sampling technique used in this study was the Axidental sampling model. Axidental Sampling is a technique for determining samples based on spontaneity factors, meaning that anyone who accidentally meets the researcher and according to their characteristics (characteristics), then the person can be used as a sample (respondent). The number of samples that will be used in the study is 50 respondents.The results of the analysis based on the partial t-test show that the proposed hypothesis is acceptable. Meanwhile, the results of the coefficient of determination analysis show a significant and positive influence between marketing strategies on sales volume